2020
DOI: 10.2319/022620-134.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic debonding and tooth sensitivity of anterior and posterior teeth:

Abstract: Objectives To assess whether orthodontic debonding and onset of tooth sensitivity were related and if anterior and posterior teeth showed different sensitivity. Materials and Methods 40 patients were divided into a trial group (group 1, at the end of the multibracket treatment) and a control group (group 2, not under treatment). After the application of compressed air and cold water to mandibular incisors and first molars, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…Contrary to our finding, Nehir et al in their study found lesser VAS score in the lower arches away from where debonding started and explained this correlation with "monotony factor" [19], which means that patient can lose interest in the procedure after the first few teeth are debonded [3]. One finding that has been previously reported in a similar context is that orthodontic debonding usually leads to enhanced tooth sensitivity mostly in the anterior region but it gradually subsides in the next few days [32]. To this effect, desensitizing agents can be applied to help reduce pain during the period after debonding [33].…”
Section: Discussionsupporting
confidence: 85%
“…Contrary to our finding, Nehir et al in their study found lesser VAS score in the lower arches away from where debonding started and explained this correlation with "monotony factor" [19], which means that patient can lose interest in the procedure after the first few teeth are debonded [3]. One finding that has been previously reported in a similar context is that orthodontic debonding usually leads to enhanced tooth sensitivity mostly in the anterior region but it gradually subsides in the next few days [32]. To this effect, desensitizing agents can be applied to help reduce pain during the period after debonding [33].…”
Section: Discussionsupporting
confidence: 85%
“…Optimal shear bond strength for orthodontic bonding should allow for little bracket failures during treatment as well as easy debonding at the end of treatment to avoid hypersensitivity due to bracket removal [26]. The shear bond strength measured for the adhesion of Filtek Silorane to unground bovine enamel was lower than the minimum forces recommended by Reynolds [27].…”
Section: Discussionmentioning
confidence: 86%
“…For instance, other bacterial strains deserve to be evaluated. Finally, due to the remineralizing effect of the zinc hydroxyapatite contained in the products, the action of the tested experimental toothpastes deserves to be evaluated also in lesions occurring in patients under active orthodontic treatment [28].…”
Section: Discussionmentioning
confidence: 99%